2000
DOI: 10.2337/diacare.23.6.733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with tomato juice, vitamin E, and vitamin C on LDL oxidation and products of inflammatory activity in type 2 diabetes.

Abstract: Abbreviations: apo(a1), apolipoprotein A1; apo(b), apolipoprotein B; CHD, coronary heart disease; C-RP, C-reactive protein; ELISA, enzyme-linked immunosorbent assay; ICAM-1, intercellular adhesion molecule 1; IL, interleukin; PBS, phosphate-buffered saline; VCAM-1, vascular cell adhesion molecule 1.A OBJECTIVE -To compare the effects of short-term dietary supplementation with tomato juice, vitamin E, and vitamin C on susceptibility of LDL to oxidation and circulating levels of C-reactive protein (C-RP) and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
7
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(241 citation statements)
references
References 26 publications
12
215
7
7
Order By: Relevance
“…CRP levels were significantly lower in the multivitamin group after 6 months, but only plasma levels of vitamin B 6 and vitamin C were inversely associated with CRP levels Contrary to our results, where no significant effect of high dose vitamin C on levels of CRP was observed, Block et al (2004) demonstrated a 17% (À0.5 mg/l) reduction of plasma CRP (24% after adjustment for baseline plasma CRP and BMI) after 2 months supplementation with high dose vitamin C in healthy adults, actively or passively exposed to cigarette smoke. Our observations of a CRP lowering effect of vitamin E from supplements in women is supported by several intervention studies: A 49% (À2.7 mg/l) significant decrease in CRP levels was shown in patients with type 2 diabetes after 4 weeks of vitamin E (800 IU), but not for vitamin C (Upritchard et al, 2000). Furthermore, CRP was significantly lower after 6 months intake of vitamin E (400 IU) in smokers with acute coronary syndrome (Murphy et al, 2004).…”
Section: Biochemical Mechanismssupporting
confidence: 65%
“…CRP levels were significantly lower in the multivitamin group after 6 months, but only plasma levels of vitamin B 6 and vitamin C were inversely associated with CRP levels Contrary to our results, where no significant effect of high dose vitamin C on levels of CRP was observed, Block et al (2004) demonstrated a 17% (À0.5 mg/l) reduction of plasma CRP (24% after adjustment for baseline plasma CRP and BMI) after 2 months supplementation with high dose vitamin C in healthy adults, actively or passively exposed to cigarette smoke. Our observations of a CRP lowering effect of vitamin E from supplements in women is supported by several intervention studies: A 49% (À2.7 mg/l) significant decrease in CRP levels was shown in patients with type 2 diabetes after 4 weeks of vitamin E (800 IU), but not for vitamin C (Upritchard et al, 2000). Furthermore, CRP was significantly lower after 6 months intake of vitamin E (400 IU) in smokers with acute coronary syndrome (Murphy et al, 2004).…”
Section: Biochemical Mechanismssupporting
confidence: 65%
“…Intervention studies have tried to clarify these ambiguous results; but these have also been inconclusive. Of those looking at the effects of vitamin E, three studies found statistically significant treatment effects [18][19][20]; and four found no treatment effect [24][25][26][27]. Most of these studies were conducted in disease state subjects, especially those which reported an effect, unlike the apparently healthy men with mildly elevated tHcy levels used in the current study; healthy subjects were also used in three of the four studies reporting no effect [24,25,27].…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, those which reported an effect often used doses of vitamin E that were higher than those employed in the current study (e.g. 200 mg/d [18], 800 IU/d [19] and 1,200 IU/d [20]). With regard to vitamin C, three studies found statistically significant treatment effects [21][22][23], and two found no treatment effect [28,29].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Upritchard et al (2000) showed a protective effect of 500 ml/day of tomato juice consumption on lipoprotein oxidation (42% increase in LDL lag time) in well-controlled type II diabetic patients.…”
Section: Mechanisms Of Action Of Lycopenementioning
confidence: 88%